Saving the Mighty Mekong - Alexis Turek (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2023)
The Mekong River has provided food, agriculture, and employment for millions of people in Southeast Asia for thousands of years. This storied history may well be coming to an end following decades of harmful Chinese damming practices, a regional overreliance on hydropower, and climate change. Severe drought, water shortages, and major biodiversity loss have led to a marked decrease in agriculture and fishing yields, which could lead to an economic downturn and/or food shortages if the current situation continues. It is in the best interest of the US to aid in mitigating these risks. Such efforts would support US goals regarding environmental protection and sustainable energy, and also provide an opportunity for US-Southeast Asian cooperation that the region will be more receptive to; as it will not require states to “choose” between China and the US.